PENGEMBANGAN MODUL DISERTAI PETA KONSEP JENIS SPYDER CONCEPT MAP PADA MATERI SISTEM GERAK MANUSIA UNTUK KELAS VIII SMP - Angkana, Yudi; Risdawati, Renny; Fitriani, Vivi (STKIP PGRI Sumbar, 2013)
ABSTRACT Â Â Module is the smallest unit learning program that systematically arranged, it can used by students independently without guidance of a teacher. The purpose of this study is to produce a module with concept map. The types concept map is spyder concept map. The subject of this research is Human Musculoscleton System for class VIII SMP. This was a developmental research with a prodecural model. Models and procedure of development was develop with 4-d model, but for something reason this research just done on develop phase. Phases are define, design and develop. This research has been implemented and tested on July 29, 2013 by two teachers and 20 students of class IX SMPN1 Ranah Batahan. The results of this study is module with spyder concept map on the subject of Human Musculoscleton System average validity of modules was 83% and practicality of modul was 85%. Based on the results, this research can be concluded that the development of modules based with spyder concept map of material in human musculoscleton system development subject is valid and practical.Â